2006
DOI: 10.1016/s1472-6483(10)61439-3
|View full text |Cite
|
Sign up to set email alerts
|

Impact of ovarian endometrioma on assisted reproduction outcomes

Abstract: The effects of ovarian endometrioma on fertility outcomes with IVF and embryo transfer have been causally related to poor outcomes. The objective of this meta-analysis was to evaluate the ovarian reserve and ovarian responsiveness to ovarian stimulation and assisted reproduction outcomes in patients with ovarian endometrioma. The odds for clinical pregnancy were not affected significantly in patients with ovarian endometrioma compared with controls, with an overall odds ratio of 1.07 from three studies [95% CI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
94
0
3

Year Published

2011
2011
2022
2022

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 142 publications
(103 citation statements)
references
References 65 publications
6
94
0
3
Order By: Relevance
“…Bu çalışmalarda antral folikül sayısı [9], ovulasyon oranı veya gonodotropinlere yanıt incelenmiştir [10,11,12]. Geniş çaplı bir derlemede ovaryan endometriomaları bulunan hastalarda kontrol gurubuna göre ovulasyon indüksiyo-nu ile daha az folikül elde edildiği görülmüştür [13]. Biz çalışmamızda ovaryan rezervi değerlendirmek için FSH, LH, E2 ve Ovaryan arter RI değerlerini kullandık.…”
Section: Discussionunclassified
See 1 more Smart Citation
“…Bu çalışmalarda antral folikül sayısı [9], ovulasyon oranı veya gonodotropinlere yanıt incelenmiştir [10,11,12]. Geniş çaplı bir derlemede ovaryan endometriomaları bulunan hastalarda kontrol gurubuna göre ovulasyon indüksiyo-nu ile daha az folikül elde edildiği görülmüştür [13]. Biz çalışmamızda ovaryan rezervi değerlendirmek için FSH, LH, E2 ve Ovaryan arter RI değerlerini kullandık.…”
Section: Discussionunclassified
“…Ayrıca yapılan çalışmalarda, kanama kontrolünün koter veya sü-tur ile karşılaştırıldığında, bipolar koter kullanımının over rezervini daha çok etkilediği belirtilmektedir. [9,10,11,13,14]. Bizim çalışmamızda laparaskopik endometrioma cerrahisinin (kanama kontrolü bipolar koter ile sağlandı) over hacmini anlamlı olarak azaltmasına rağmen kan akım indeksinde herhangi bir değişik-liğe neden olmadığını gördük.…”
Section: Discussionunclassified
“…Endometriosis affects oocyte number but not embryo quality or pregnancy rates and outcome, whether or not an endometrioma is present [18] . Endometrioma has adverse effects only on follicle number and oocytes quality [69] . Yang et al [70] showed same results but less total number of embryos and M2 oocytes.…”
Section: In-vitro Fertilization (Ivf)mentioning
confidence: 99%
“…Increasing numbers of women with endometriosis have achieved pregnancy with assisted reproductive technology (ART). Several studies have suggested that the presence of an endometrioma reduces the quality of the oocytes, as reflected by the reduced rate of fertilization and implantation after controlled ovarian hyperstimulation and in vitro fertilization (IVF) treatment 4, 5, 6, 7. The European Society of Human Reproduction and Embryology guidelines state that there is no evidence that cystectomy prior to treatment with ART improves the pregnancy rates in infertile women with endometriomas that are >30 mm.…”
Section: Introductionmentioning
confidence: 99%